2009
DOI: 10.1111/j.1365-4632.2009.03994.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein (a) in patients with psoriasis: associations with lipid profiles and disease severity

Abstract: Lp(a) may be a factor contributing to an increased cardiovascular risk in patients with psoriasis. A pathogenetic link may exist between this lipoprotein and psoriatic pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 63 publications
1
25
1
3
Order By: Relevance
“…19 Psoriatic patients also had elevated levels of lipoprotein (a) after controlling for hyperlipidemia. 21 Overall, the preponderance of data supports this association with dyslipidemia.…”
Section: Cvd Risk Factors Associated With Psoriasismentioning
confidence: 59%
“…19 Psoriatic patients also had elevated levels of lipoprotein (a) after controlling for hyperlipidemia. 21 Overall, the preponderance of data supports this association with dyslipidemia.…”
Section: Cvd Risk Factors Associated With Psoriasismentioning
confidence: 59%
“…Wielu autorów wykazało zwiększo-ne stężenie apolipoprotein (apo A1, apo B, apo C i apo E) w surowicy chorych na łuszczycę [35][36][37]. Niektórzy nie obserwowali zmian w porównaniu z grupą kontrolną [38,39], inni stwierdzili zmniejszenie ich stężenia [34].…”
Section: Lipidy W Surowicy Cholesterole Trójglicerydy I Apolipoproteinyunclassified
“…Many authors have shown elevated concentrations of apolipoproteins (apo A1, apo B, apo C and apo E) in the serum of patients with psoriasis [35][36][37]. Some studies have found no change relative to the control group [38,39], and others have shown a decrease in apolipoprotein levels [34].…”
Section: Lipidy W Surowicy Cholesterole Trójglicerydy I Apolipoproteinymentioning
confidence: 99%
“…In most studies, elevated levels of apoA1, apoB [16, 43], apoC3, and apoE [41, 7678] were detected in the serum of psoriatic patients compared to the healthy control group. However, there are also contrary results showing decreased levels of apolipoproteins [79].…”
Section: Apolipoproteinsmentioning
confidence: 99%